Assessment of consumers acceptability and its socio-economic effect on their patronage at U&I fast food in the University of Ibadan, Oyo State, Nigeria (2016)
This study assessed the food acceptability at the U&I Fast Food in the University of Ibadan and the socio-economic effect of fast food at the selected centre (U&l fast food) University of Ibadan, The result showed that consumers who are under 20 years of age constitutes the major age group with 43.1% and those in age bracket 31-40 constitutes the major age group with 40% for staff at the fast food, 65% of the consumers wire females while 35% were males. Also, a higher percentage earn between 51000 - 90000 Naira and 100000 - 500000 Naira for staff and consumers respectively. The level of education of most of the consumers was tertiary education and those of ' the staff were secondary education at 86% and 45% respectively. They represented45% of staff and 98% of students. The higher percentage of students could be associated.to the closeness to, Hall of Residence. The study showed that consumers were highly aware of food at the fast food, joint at 87%. This study showed that consumers patronize the fast food joint because of one of - these factors: clean environment, taste, cheapness, appealing, quality, flavour and also because of their texture, hygienic practices and preparation.